The Reaction of 1,6-Diamino-4-aryl-2-oxo-1,2-dihydropyridine- 3,5-Dicarbonitriles with Certain Electrophilic Agents - Alexei A. Dolganov; Alexandra R. Chikava; Victor V. Dotsenko (Chemistry Proceedings)
The reaction of 1,6-diamino-2-oxo-1,2-dihydropyridine-3,5-dicarbonitriles, which are easily available through the reaction of cyanoacetohydrazide with arylmethylene malononitriles, with ninhydrin leads to the formation of novel dihydroindeno[1,2-e]pyrido[1,2-b][1,2,4]triazines. Another active carbonyl compound, glyoxal, reacts with 1,6-diamino-2-oxo-1,2-dihydropyridine-3,5-dicarbonitriles under mild conditions to give functionalized 6-oxo-6H-pyrido[1,2-b][1,2,4]triazine-7,9-dicarbonitriles.